June 2010 LSAT
Section 5
Question 14

June 2010 LSAT
Section 5
Question 14

Reply

Irina on September 20, 2019

@jbelcher,Let's look at these examples. It is not necessary to write out the contrapositive of every premise, rather look for common elements:

(1) Y -> C

(2) ?

(3) A -> ~B

(4) Therefore, B -> C

Let's start by taking a contrapositive of (3) to match it with B in the conclusion:

(5) B -> ~A

Now, how do we get from B -> ~ A to B -> C, we need to connect ~A to C. Per (1) Y -> C, thus the missing premise must be ~A - > Y.

Taken together these premises will result in the following chain:

B-> ~A

~A -> Y

Y-> C

B-> ~A -> Y-> C

Therefore, B-> C.

For example 2:

(1) D ->A

(2) C ->D

(3) ?

(4) Therefore, ~X -> A

Note that (1) and (2) have a common element D, thus we can make the following inference from (1) and (2):

C -> A

Now how do we make an inference from C->A to our conclusion ~X -> A, we need to connect ~X and C:

~X -> C

The resulting premises:

~X -> C

C -> A

allow us to infer the conclusion:

~X -> A .

Let me know if this makes sense and if you have any further questions.

GET $100